Fashion brands and gay/lesbian-inclusive advertising in the USA. Issue 2 (1st March 2016) - Chae, Yoori; Kim, Yumin; Johnson, Kim K. P.
Within the United States general attitudes towards gays and lesbians (GL) are rapidly undergoing change. Several researchers have previously documented that heterosexual consumers respond negatively to advertisements featuring same-sex couples. At this critical juncture, it is important to reexamine consumer response to fashion advertisements featuring GL images. Using a small qualitative study (n = 10) and an experiment (n = 202) our research purpose was to determine whether consumer attitude towards advertisements, brand attitude, brand distinctiveness and/or brand attractiveness varied based on the level of inclusiveness of GL images (i.e. GL-inclusive vs. non-inclusive). Results from the qualitative project demonstrated most participants responded positively to the advertisements featuring GL images although two participants were worried about unidentified 'negative' influences on the sexual orientation of heterosexual viewers. The inclusiveness level of GL images did not negatively influence attitude towards the advertisements or brand attitude. Rather, GL-inclusive advertising resulted in higher ratings of brand distinctiveness and attractiveness as compared to the non-inclusive advertising. Implications and limitations of this study as well as suggestions for future research are discussed.